PENGEMBANGAN MEDIA PEMBELAJARAN RPG BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Yuliana, Rosa; Salsabila, Ellis; Aziz, Tian Abdul (LPPM Universitas Bina Bangsa, 2024)
Development of android-based RPG learning media to improve students' mathematical problem solving skills. This research uses research and development methods. Sampling is done using purposive random sampling. research emphasis means students in class VII Mekarsari Junior High School. The results of the study (1) RPG learning media based on android is very valid, with a percentage of validity of 92% material and 82% media. (2) RPG learning media based on android is very practical, using a teacher response questionnaire of 85% and students 92%. (3) the calculation results increased and effective, using tcount> ttable = 8.859> 1.717. using this, Ho is rejected Ha is accepted. using this, android-based RPG learning media can increase learning that will occur and be effective.